Pandemics in the past Eight Centuries: A Sociological Appraisal - Mohammad Taghi Sheykhi; Muhammad Ridwan (Budapest International Research and Critics University, 2021)
The present article intends to reflect the appearance of different pandemics in different periods from sociological point of view. Earlier pandemics used to appear without being able to control them; at the historical times without medications, hospitals, motor vehicles, without communications etc. Millions of people died because of spreading unknown diseases such as flu, cholera, black death, plague and the like. Estimates show that the first 15 events killed over 85 million people. Plague in Italy during some years in the 17th century perished many people vs the least of facilities within reach. Similarly, great plague in Spain in mid 17th century took the lives of a large number of people. Great plague of London also in the second half of the 17th century killed more than 100,000 of citizens. Such events not only directly killed older household members, but created bad lives and deprivation for the younger remaining members in such households. Many of such children had to resort to orphanages. Cholera outbreak also appeared in early 19th century in India, Russia and Africa leaving behind a great number of deaths. The flu pandemic at the end of 19th century killed many people. Many countries came to know more on influenza since then. The outbreak of Coronavirus in 2020 is the worst very widespread and global affecting and infecting many people in all corners of the world. Coronavirus pandemic is wide spreading without being prevented. Despite all the existing facilities, it is killing more than the earlier pandemics in terms of time and space. As education and understanding of people are currently higher than before, they highly feel distressed and disordered.